Development of interactive learning media using lectora inspire 17.0 through e-learning - Ratumas Ayu Atika Putri; K. Krismadinata; Rijal Abdullah (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
This article discusses the interactive learning media development through E-Learning courses on Electrical power. Media interactive learning through E-Learning is designed to be able to improve the learning results of students on courses of electronics power. This study uses the methods of Research and Development (R and D), and procedures development of Instructional Development Institute (IDI) which includes three phases, namely (1) define, develop, (2) and (3) evaluate. The type of data that is primary data where data provided by media experts, professors, and students. Data analysis techniques used are descriptive data analysis technique that is by describing the validity, practicality and effectiveness of media interactive learning through E-Learning. Media interactive learning through E-Learning is designed using Lectora Inspire 17.0. The results of this study indicate that interactive learning media Lectora Inspire 17.0 through E-Learning is valid, practical, and effective.